2010
DOI: 10.1007/s10552-010-9591-9
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal exposures and the risk of uveal melanoma

Abstract: The results of this study do not support the hypothesis of a hormonal influence in the carcinogenesis of uveal melanoma. Our finding of a potentially increased risk with PCB-containing oils requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 27 publications
2
34
2
Order By: Relevance
“…While in these industries, workers may be exposed to several possible carcinogenic agents, the observed excess risks were not explained by exposure to EDC. In conclusion, taking into account our previous inconsistent findings on a possible association between hormonal factors and uveal melanoma (14,17,19), the present study does not support the hypothesis that hormonal influences are an important factor in the aetiology of these tumors.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…While in these industries, workers may be exposed to several possible carcinogenic agents, the observed excess risks were not explained by exposure to EDC. In conclusion, taking into account our previous inconsistent findings on a possible association between hormonal factors and uveal melanoma (14,17,19), the present study does not support the hypothesis that hormonal influences are an important factor in the aetiology of these tumors.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, misclassification of one or two case subjects when dealing with low prevalence may even bias estimates towards a spurious positive association. This is potentially illustrated by the contrasting findings we observed with respect to PCB: previous analyses from this study using questions from the core questionnaire found occupational PCB exposure to be a risk factor for uveal melanoma (14), while no risk was indicated when applying PCB-related questions from JSQ across two different industries (electro techniques and tire and rubber production) in the present analysis. However, one advantage of this study, with exposure estimates based on individually solicited JSQ, is the higher specificity in the assessment of job-related exposures as compared to, eg, JEM or job titles.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The original study of the Indiana plant noted that PCB-exposed workers were at greater risk of skin effects, including chloracne and hyperpigmentation (Sinks et al, 1992). Several recent papers support an association of melanoma and PCB exposure: Behrens and colleagues observed an increased risk of uveal melanoma among men with occupational exposure to transformer or capacitor oils (odds ratio 2.74, 95% CI 1.07-7.02) (Behrens et al, 2010); Gallagher et al saw a doseresponse effect for melanoma risk and plasma levels of PCBs (p for trend <0.001), comparing melanoma patients and controls (Gallagher et al, 2011); and Loomis and colleagues reported increased melanoma risk among electrical utility workers exposed to PCBs (Loomis et al, 1997). A review (which included the original study of the Indiana cohort (Sinks et al, 1992)) of non-solar occupational risk factors for melanoma found increased risks for workers in the electric and electronic industry (Fortes and de Vries, 2008).…”
Section: Discussionmentioning
confidence: 96%